Virtual HSM: Building a Hardware-backed Dependable Cryptographic Store - Rosa, Miguel Gomes (2019)
Cloud computing is being used by almost everyone, from regular consumer to IT specialists, as it is a way to have high availability, geo-replication, and resource elasticity with pay-as-you-go charging models. Another benefit is the minimal management effort and maintenance expenses for its users. However, security is still pointed out as the main reason hindering the full adoption of cloud services. Consumers lose ownership of their data as soon as it goes to the cloud; therefore, they have to rely on cloud provider’s security assumptions and Service Level Agreements regarding privacy and integrity guarantees for their data. Hardware Security Modules (HSMs) are dedicated cryptographic processors, typically used in secure cloud applications, that are designed specifically for the protection of cryptographic keys in all steps of their life cycles. They are physical devices with tamperproof resistance, but rather expensive. There have been some attempts to virtualize HSMs. Virtual solutions can reduce its costs but without much success as performance is incomparable and security guarantees are hard to achieve in software implementations. In this dissertation, we aim at developing a virtualized HSM supported by modern attestation-based trusted hardware in commodity CPUs to ensure privacy and reliability, which are the main requirements of an HSM. High availability will also be achieved through techniques such as cloud-of-clouds replication on top of those nodes. Therefore virtual HSMs, on the cloud, backed with trusted hardware, seem increasingly promising as security, attestation, and high availability will be guaranteed by our solution, and it would be much cheaper and as reliable as having physical HSMs.